PENGARUH HARGA, PROMOSI, DAN INOVASI TERHADAP LOYALITAS PELANGGAN GO-JEK DI JAKARTA TIMUR - Tasya Salsabila Kadis; Ajad Sudrajat (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The aim of the research is to find out what things are affected in the success of the Go-Jek company, especially in terms of price, promotion, and innovation. This type of research is quantitative, with both variables, namely the independent variable and also the dependent variable, the independent variable is Price, Promotion, and Innovation, and Customer Loyalty is the dependent variable. In this study, there were 222 populations who used Go-Jek in their lives, but only 100 were sampled. The results of this study are that customer loyalty is indeed influenced by price, promotion, and innovation. The more balanced the price applied by the company to Go-Jek users, the more the trust and interest of Go-Jek service user customers in Go-Jek will increase, and not only that, promotions also affect the attractiveness and interest of Go-Jek user customers, because the more new promotions that are launched, it will attract the interest of the customers themselves to become loyal customers, especially to Go-Jek itself, and the last is on the display of innovation, innovation has a big influence on Go-Jek customer loyalty, because the more new ideas and new changes for the better, it will make Go-Jek users become loyal users while on the market, so that Go-Jek is able to compete in the market and is not worried that its customers will experience a decline.